2007
DOI: 10.1111/j.1475-097x.2007.00739.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of multidirectional mechanical vibration on peripheral circulation of humans

Abstract: The physiological response of humans to vibration has intrigued researchers for some time, and recently in relation to its potential as a non-pharmacological means to improve peripheral blood flow. A new vibration device [Arapal Technologies Ltd (ATL), Christchurch, New Zealand] for pain relief that purportedly delivers multidirectional vibration waveforms, has been developed. The aim of the study was to quantify the effect of 30 min of mechanical vibration (60 Hz) using two ATL massage devices concurrently up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 11 publications
2
48
1
4
Order By: Relevance
“…In diabetic patients, and in contrast to Lythgo et al (12) findings on healthy subjects, Johnson et al (15) showed low frequency (26 Hz) and low amplitude (2 mm) vibration increased blood flow (to the skin area in the feet). Similarly, Sañudo et al (16) revealed significant improvement of femoral artery blood flow after 12 weeks of WBV training in diabetic patients (12)(13)(14)(15)(16) Hz, 4 mm, 3 days a week). Whether WBV can have a positive effect on local blood flow of diabetic patients remains controversial and requires further investigation.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…In diabetic patients, and in contrast to Lythgo et al (12) findings on healthy subjects, Johnson et al (15) showed low frequency (26 Hz) and low amplitude (2 mm) vibration increased blood flow (to the skin area in the feet). Similarly, Sañudo et al (16) revealed significant improvement of femoral artery blood flow after 12 weeks of WBV training in diabetic patients (12)(13)(14)(15)(16) Hz, 4 mm, 3 days a week). Whether WBV can have a positive effect on local blood flow of diabetic patients remains controversial and requires further investigation.…”
Section: Introductionmentioning
confidence: 86%
“…Lythgo et al (12) suggested the increased leg blood flow accompanying WBV in healthy volunteers was related to high frequency and high amplitude of vibration. However, using high frequency, Button et al (13) and Hazell et al (14) reported no significant difference in local blood flow in healthy participants between vibration and control groups. In diabetic patients, and in contrast to Lythgo et al (12) findings on healthy subjects, Johnson et al (15) showed low frequency (26 Hz) and low amplitude (2 mm) vibration increased blood flow (to the skin area in the feet).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Drogą odruchową zachodzą zmiany w układzie nerwowym. Usprawnienie krążenia obwodowego wpływa na usuwanie obrzęku tkanek [6]. Warto zwrócić uwagę na to, że masaż wibracyjny zapewnia rozluźnienie mięśni, zaś jego działanie ogólne może także polegać na relaksacji -obniżeniu napięcia emocjonalnego.…”
Section: Masaż Wibracyjny Mechaniczny Miejscowyunclassified
“…Through this refl ex way changes in the nervous system occur. Improving of the peripheral circulation facilitates reduction of oedema of tissues [6]. It should be emphasised that vibratory massage provides muscle relaxation and general effects may also include decreasing of emotional tension.…”
Section: Mechanical Local Vibratory Massagementioning
confidence: 99%